Analysis of 20 genotypes of bread wheat in the Yaqui Valley, Sonora - Velasco Magallanes José Enrique; Pérez López Delfina de Jesús; Rajaram Devi, Sanjaya; Balbuena Melgarejo, Artemio; González Huerta Andrés (Revista Mexicana de Ciencias Agrícolas, 2018)
The work was conducted in the cycle autumn-winter 2008, under irrigated conditions in two sites in the Yaqui Valley, Sonora, Mexico, to assess 17 lines of bread wheat and three cultivars (control) for their grain yield, yield components and resistance to rust. The genetic material was evaluated in field in a randomized complete block with four replications per location. The variables recorded were: grain yield (GY), flowering (DF), physiological maturity (PM), plant height (PH) and incidences of lodging (IL) and leaf rust (LR). Data were subjected to analysis of variance individually and combined, comparison of treatment means with the Tukey test (α= 0.01) and to the main component analysis. Higher yielding lines were RSMF7CJ-62 (8.32 t ha-1 in block 609), and BABAX/ LR42 (7.53 t ha-1 in block 1605). If selection was made by grain yield the outstanding genotypes would be RSMF7CJ-92 (7.78 t ha-1), BABAX / LR42 (7.75 t ha-1) and RSMF7CJ -78 (7.74 t ha-1). The lines 01W20728 and Strong White are dwarfs, 05W90710, RSMF7CJ-90 and RSMF7CJ -92 are semi-dwarf and the remaining 13 and the three controls are tall. The genotypes were statistically equal in incidence of rust and the highest values were registered in Tacupeto (1.65%), 05W90685 (1.29%), Roelf (1.11%), 05W90710 (1.02%) and Kronstad (1.02%).